MOOD R Technique - Tsoutsanis, Panagiotis; Nogueira, Xesus; Farmakis, Pericles (Cranfield University, 2020)
This a representative data-set from the results obtained with the development of the MOOD technique for the UCNS3D code.the results from the following test problems are included in tecplot format that can be used with tecplot and paraview for visualisation and further post-processing 1) 2D implosion 2) 2D explosion 3) Vortex Evolution 4) Double Mach Reflection
Keywords: CFD methods; Unstructured; Finite-Volume Method; implosion; explosion; vortex motion; Computational Fluid Dynamics